Android-Based Elementary Linear Algebra Learning Media - Haikal Nadhar Bidawi (Pascasarjana UIN Sumatera Utara, 2022)
This research is driven by the importance of android-based learning media in Elementary Linear Algebra learning, namely facilitating student understanding in understanding the existing material, because students do not understand the learning conveyed by the lecturer and the time is short, this can reduce student interest and have difficulty in understand the material. This study uses the Research and Development method using the Luther Sutopo model. The product was tested using Aiken's